Allocation trade-off under climate warming in experimental amphibian populations - Gao, Xu; Jin, Changnan; Camargo, Arley; Li, Yiming (PeerJ, 2015)
Climate change could either directly or indirectly cause population declines via altered temperature, rainfall regimes, food availability or phenological responses. However few studies have focused on allocation trade-offs between growth and reproduction under marginal resources, such as food scarce that may be caused by climate warming. Such critical changes may have an unpredicted impact on amphibian life-history parameters and even population dynamics. Here, we report an allocation strategy of adult anuran individuals involving a reproductive stage under experimental warming. Using outdoor mesocosm experiments we simulated a warming scenario likely to occur at the end of this century. We examined the effects of temperature (ambient vs. pre-/post-hibernation warming) and food availability (normal vs. low) on reproduction and growth parameters of pond frogs (Pelophylax nigromaculatus). We found that temperature was the major factor influencing reproductive time of female pond frogs, which showed a significant advancing under post-hibernation warming treatment. While feeding rate was the major factor influencing reproductive status of females, clutch size, and variation of body size for females, showed significant positive correlations between feeding rate and reproductive status, clutch size, or variation of body size. Our results suggested that reproduction and body size of amphibians might be modulated by climate warming or food availability variation. We believe this study provides some new evidence on allocation strategies suggesting that amphibians could adjust their reproductive output to cope with climate warming.
Keywords: Trade-off; Allocation strategy; Reproduction; Climate change; Food availability; Experimental warming; Feeding rate; Phenology; Mesocosm; Climate warming